Pelatihan Branding dan Pembukuan Digital Sebagai Pengabdian Masyarakat Terhadap Pengembangan UMKM Desa Tegalrejo - Eka Amelia Puspita; Dra Siti Ning Farida (BADAN PENERBIT STIEPARI PRESS, 2023)
UMKM is a trading business that is managed individually. And from the survey results, it can be seen that there are more than 20 SMEs with various types of existing businesses. Most of the businesses that are run are designing or grocery stores. Apart from that, there are also many umkm with processed food. Of the many SMEs, many still lack knowledge about branding and bookkeeping. Therefore, the purpose of this service is to help SMEs in Tegalrejo Village, especially UMKM Bila Catering and UMKM Tahu Tempe Pantura in the business development process in the form of product branding and digital bookkeeping. The methods used are survey methods, socialization, and mentoring. The result of this activity program is that MSME actors understand and understand more about what needs to be done in the business development process. As well as MSME actors can develop the next product branding and can record finances easily and quickly independently by using digital bookkeeping through the shop book application.